Quality Assessment and Content Analysis of Youtube Videos on Glaucoma Surgery (British Journal of Multidisciplinary and Advanced Studies, 2022)
The aim of this study is to evaluate the accuracy, quality and reliability of the videos on glaucoma surgery on YouTube which is an online video-sharing platform.The material has been obtained by a video search carried out on the Youtube -online video platform- with the keyword “Trabeculectomy” is kind of glaucoma surgery. A total of 44 videos for the keyword “trabeculectomy” were analyzed. When evaluated according to the exclusion criteria, a total of 10 videos were included in the analysis, and the 34 videos were excluded. Thus, after carving out the secondary data, a number of statistical analyses were performed namely Shapiro-Wilks, Kruskall-Wallis, Mann-Whitney U and Backward Linear Regression. In this framework, statistical analyzes were made via using the Stata software. Statistical significance value (threshold) was accepted as %10 (p